2011
DOI: 10.1200/jco.2010.34.3426
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Stage II Colon Cancer With Poor Prognostic Features

Abstract: Purpose Adjuvant chemotherapy is typically considered for patients with stage II colon cancer characterized by poor prognostic features, including obstruction, perforation, emergent admission, T4 stage, resection of fewer than 12 lymph nodes, and poor histology. Despite frequent use, the survival advantage conferred on patients with stage II disease by chemotherapy is yet unproven. We sought to determine the overall survival benefit of chemotherapy among patients with stage II colon cancer having poor prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
298
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(319 citation statements)
references
References 36 publications
13
298
2
6
Order By: Relevance
“…A study by O'Connor and colleagues showed that 75% of the 24,847 stage II cancers had one or more poor prognostic features of perforation, T4 stage, poor histology, or others, and that survival benefit from adjuvant chemotherapy was not observed even with any poor prognostic features (32). The findings indicate that prognostic factors do not always predict patients' survival benefit by adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…A study by O'Connor and colleagues showed that 75% of the 24,847 stage II cancers had one or more poor prognostic features of perforation, T4 stage, poor histology, or others, and that survival benefit from adjuvant chemotherapy was not observed even with any poor prognostic features (32). The findings indicate that prognostic factors do not always predict patients' survival benefit by adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 86%
“…Currently, patients with stage II colonic cancer are treated mostly by surgery alone. However, patients with high-risk stage II disease, with a prognosis similar to stage III patients, should be offered chemotherapy under the current guidelines (O'Connor et al 2011). In spite of the potentially curative resection, about 15-30% of patients with stage II disease will eventually develop recurrent locoregional disease or distant metastases within 5 years (Koebrugge et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…El porcentaje de pacientes en etapa II y III que recibió QT en esta serie fue de 22 y 70% respectivamente. Esto es similar a la frecuencia reportada por un estudio americano utilizando la base de datos del SEER (Surveillance, Epidemiology, and End Results) que incluyó a más de 23.000 etapa II y 17.000 pacientes en etapa III 22 . Los datos obtenidos en nuestro estudio reproducen la sobrevida alcanzada en estudios aleatorizados internacionales en esta patología 5,9,10 .…”
Section: Tratamiento Y Sobrevidaunclassified